Food in correctional facilities: A scoping review - Smoyer, Amy B. (Appetite, 2019)
In the last 20 years, there has been an exponential increase in research about food in prison. Given this growing interest, it is appropriate to take stock of the field by mapping and synthesizing existing knowledge in order to identify gaps in knowledge and make recommendations for future research. Specifically, the purpose of this scoping review is to understand the experiences of incarcerated people with food in order to inform interventions that will promote positive outcomes for justice-involved individuals and correctional facilities. This review identified 38 peer-reviewed research articles about food in correctional facilities. This sample included qualitative (n = 28) and quantitative (n = 10) research that explored the both the pragmatic and symbolic dimensions of food in these settings. Taken together, this body of research provides a rich description of prison food practices and the implications of these practices on medical, psychological, and sociological outcomes. Moving forward, collaboration between academics, incarcerated people, and correctional practitioners is encouraged in order to develop programs that use this research to improve individual and intuitional outcomes. In addition, while emerging research has begun to develop knowledge about prison food in developing countries, the literature focuses primarily on the US, Canada and Western Europe and there is a need to expand the geographic scope of this inquiry.
Keywords: *Food Services; *Prisons; Canada; Consumer Behavior; Europe; Food Services; Humans; Nutritive Value; Prisons; United States; Western Europe; adult; article; catering service; clinical article; consumer attitude; dept.swk; developing country; female; human; justice; male; nutritional value; peer-reviewed; physician; prison